2013
DOI: 10.1088/0268-1242/28/4/045014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of group-III donors on high-resolution photoluminescence and morphology of ZnO nanowires grown by metalorganic vapour phase epitaxy

Abstract: Extremely sharp low temperature photoluminescence (PL) linewidths as low as 0.17 meV are observed in nominally undoped ZnO nanowires grown by metalorganic vapour phase epitaxy (MOVPE). These are among the narrowest lines reported for ZnO PL, even for bulk growth, despite growth on highly mismatched sapphire substrates. MOVPE allows the control of group III dopants over a wide range of doping levels. At low concentrations the addition of indium and aluminum dopant resulted in the appearance of their correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…[1] The line positions of these transitions are in agreement with previous reports on bulk ZnO crystals and intentionally doped nanowires. [1,4,5]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The line positions of these transitions are in agreement with previous reports on bulk ZnO crystals and intentionally doped nanowires. [1,4,5]…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Bound exciton transitions associated with group III donor impurities such as Al, Ga and In were unambiguously identified with controlled intentional doping experiments. [1][2][3][4][5][6][7] These characteristic transitions were previously denoted as I-lines and identified as arising from neutral (D 0 X) and ionized (D + X) donor bound-exciton transitions. D 0 X (I 6 , I 8 , and I 9 ) and D + X (I 0 , I 1 and I 2 ) of the substitutional group III donors Al, Ga and In donors are now well established.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [4,30,34], spontaneously formed ZnO NWs crystallize in the thermodynamically stable wurtzite phase, elongate along the caxis, and exhibit abrupt sidewall facets formed by {1 100} planes (known as Mplanes). The cross-sectional shape of our ZnO NWs is compatible with these expectations.…”
Section: Morphology and Coalescence Degreementioning
confidence: 99%
“…Specifically, it was demonstrated that the coalescence process leads indeed to the formation of dislocation networks [18,19,25,26], which act as a source of non-radiative recombination, as well as to the introduction of both inhomogeneous [18,21] and homogeneous strain [23]. NW coalescence was also recognized in the case of ZnO, but has received much less attention [27][28][29][30][31]. Particularly, no attempts were made to unambiguously quantify the coalescence degree or to systematically correlate this effect with the structural perfection and luminescence properties of NW ensembles.…”
Section: Introductionmentioning
confidence: 99%
“…Problems like the study of the width and profile of an acoustic Raman peak, 8 the characterization of complex non-periodic structures through their Raman spectrum, 9 or the analysis of the isotopic effects in gases 10 and ultra-pure crystals 11,12 require a resolution close to 0.01 cm −1 or better. Other investigations that could benefit from higher resolution optical spectra include the study of donors/acceptors energies in semiconductors through photoluminescence, 13,14 the analysis of anharmonic effects in optical phonons, 15 and the characterization of single molecules via surface enhanced Raman scattering (SERS). 16,17 This would normally involve the use of specific ultra-high resolution Raman spectroscopy systems, like double spectrometers of very long focal distance 12,18 or one of several Fabry-Pérot (FP) 19,20 and FP/spectrometer tandem configurations.…”
Section: Introductionmentioning
confidence: 99%